Analysis of tribological properties and promising research of non-metallic sliding bearings - Дыха, O. В.; Вельбой, В. П.; Дитинюк, В. О. (Problems of Tribology, 2019)
Bearings made of metal antifriction materials were the most commonly used for the manufacture of pillars of slipping of technological and transport vehicles. The practice of using bearings made of metal alloys shows that they have a high wear resistance only in the case of limiting or liquid lubrication. Lubrication of food, textile, paper, pharmaceutical and chemical industries is complicated due to the negative impact of lubricants on the quality of finished products. The efficiency of the friction units of such mechanisms is ensured by the use of non-metal slide bearings, which are capable of operating under conditions of dry friction, the presence of aggressive media. Taking into account economic and environmental factors, the prospective study of antifriction materials should be considered as the development and study of tribological logic properties of such materials on the basis of natural wood. As a result of analysis of materials and technology of wood-polymer compositions, it has been shown that studies are aimed only at studying the influence of synthetic filler and other additives on the tribo technical characteristics of the bearings of sliding. Promising to improve the tribo technical properties of wood-polymeric compositions for sliding bearings is the search for cheap natural materials that, by their properties, are positively different from shredded waste wood processing